Scars, The Surgeons’ Overlooked Threat From Hero to Zero - Perdanakusuma, David S (Jurnal Plastik Rekonstruksi, 2013)
Scar is a reminding mark left by surgeons on patients who presented with wounds or required surgery. In healing process, due to some circumstances and individual traits, wounds could become bad scars that would definitely affect the patient’s appearance and cause many complaints. In the first years after treatment, surgeons will be commemorated as heroes who once helped the patients to overcome and cure the disease. After a few years, the memory of the surgeon’s heroic action will gradually dissipate with the formation of a bad scar. Such good memory will be replaced with persistent complaints arising from the scar such as deformity, pain, itchiness and enlargement of the lesion. Several efforts have been made to manage disturbing scars however they often do not yield satisfactory result and moreover sometimes the scars will enlarge, become unpleasant and more disturbing. This will frustrate the patient as well as the surgeon. The good memory of the surgeon as a hero has shifted into one whose surgical procedure was regretted. Presently, there are about 25 modalities using various approaches for scar treatment. These manifold choices indicate that the available modalities have been generally inadequate and the therapeutic response very variable. Furthermore, treatment selection is also based on recurrence. Most of the available therapeutic modalities in this stage are nonsurgical. There is also topical treatment mostly containing herbal extract, which is considered inadequate and lacking of evidence base. Corticosteroid injection and silicone gel is a nonsurgical method recommended and supported by evidence based. This technique is largely chosen by doctors. Combined therapy is the method of choice believed to yield optimal result. Let us remain heroes by paying attention to scars.